Pengembangan Bahan Ajar Digital Berbasis Anyflip pada Elemen Fase E untuk SMK Akuntansi Kelas X - Dewi Retno Dewanti; Siti Kholisatun Nazilah; Luqman Hakim; Amirul Arif (Journal on Education, 2025)
In line with technological advances, education, which is the main foundation in improving the quality of human resources, should also be able to adapt to technology. One of them is compiling digital-based teaching materials. This study aims to develop teaching materials in the form of interactive e-handouts based on the anyflip application on basic accounting material for class X phase E with elements of business processes in the field of accounting and institutional finance. This development research applies the 4-D research model such as the theory of Thiagarajan, Semmel, and Semmel which includes: the definition stage (define), the design stage (design) the media development stage (develop), and the dissemination stage (dissaminate). The e-handout teaching materials are arranged in an interesting way and highlight important points to make it easier for students to understand the material. Teachers must also continue to innovate in compiling teaching materials to meet the different needs of students. The output of this study is an e-handout that can be accessed online anytime and anywhere so that it can help students to learn independently.